Analisis Pendapatan Dan Faktor Produksi Usahatani Ubikayu Berdasarkan Pasar Yang Dipilih Petani (Study Kasus Petani di Kabupaten Lampung Tengah) - Nuni Anggraini; Harianto Harianto; Lukytawati Anggraeni (Politeknik Negeri Lampung, 2017)
The success of a farm can be seen from the amount of income and a combination optimum factors of production. The objectives of this study were to analyze the cassava farm income and to identify the factors that influence the production of cassava farming in Central Lampung Regency. This study was conducted in Central Lampung Regency, Lampung Province as center of cassava production with select 78 cassava farmers. R/C ratio and Cobb Douglas Production Function analysis was used in this study. The results revealed that income cassava farmers who sell their crops to the plant is greater than the income of farmers who sell to traders. Factors affecting on cassava production are land, seed, N fertilizer, K fertilizer and marketing channels dummy. Based on the value of return of scale in the amount of 1.30, implying that the cassava farming in Central Lampung Regency is located on Increasing Return to Scale (IRS). The income of cassava farming can be enhanced through the harvesting of cassava as recommended so as to reduce the magnitude of rafaksi.Â Keywords : Production, farming, cassava, income, cobb-douglas